Magnesium glycinate
Patent Information
- Application Number
- JP2026058217
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2026-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0020】 本開示のグリシン酸マグネシウムは、圧縮成形性が良好である。
Smart Images

Figure 2026167643000001_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to magnesium glycinate and a method for producing the same. [Background technology]
[0002] Magnesium glycinate has excellent bioavailability and weak side effects such as laxative effects, making it suitable for use in foods, nutritional supplements, pharmaceuticals, and other products.
[0003] Patent Document 1 describes a magnesium glycinate hydrate having a structure represented by the following formula. [ka]
[0004] Patent Document 2 describes a method for obtaining an insoluble metal organic chelate by adding an organic acid ligand and a metal compound to a non-aqueous liquid to form a suspension, reacting the organic acid ligand and the metal compound, heating the suspension while stirring for a predetermined time, and filtering the suspension.
[0005] Patent Document 3 describes a method for inducing a solid reaction to form a metal chelate by exposing a solvent-free mixture of a metal compound and a solid organic acid containing chelate-forming acids such as α- and β-amino acids and hydroxycarboxylic acids to strong mechanical stress. [Prior art documents] [Patent Documents]
[0006] [Patent Document 1] U.S. Patent No. 2014 / 0186408 [Patent Document 2] Japanese Patent Publication No. 2005-145822 [Patent Document 3] Special Publication No. 2020-517602 [Overview of the project] [Problems that the invention aims to solve]
[0007] Conventional magnesium glycinate usually exists as crystals. Because these crystals do not have sufficient compressibility, attempting to manufacture tablets using these crystals has drawbacks such as the size of each tablet increasing and the number of tablets required to obtain the desired effect. This disclosure has been made in view of these circumstances and aims to provide magnesium glycinate with good compressibility. [Means for solving the problem]
[0008] The first embodiment of this disclosure provides magnesium glycinate in which, in an X-ray powder diffraction spectrum, S1 is the area of amorphous peaks having a maximum value in the range 20°≦2θ≦30° and a full width at half maximum of 2° or more, and S2 is the area obtained by subtracting the sum of the areas of peaks attributed to magnesium hydroxide in the range 5°≦2θ≦70° from the sum of the areas of crystalline peaks having a maximum value in the range 5°≦2θ≦70° and a full width at half maximum of less than 1°, and the crystallinity expressed as S2 / (S1+S2) is between 0 and 0.9.
[0009] In a second embodiment of this disclosure, in the first embodiment, the thermogravimetric analysis of magnesium glycinate, with respect to the weight at 50°C, the weight reduction rate at 400°C may be 40% by mass or less.
[0010] In the third embodiment of this disclosure, in any one of the embodiments described in the first to second embodiments, the crystallinity of magnesium glycinate may be 0 or more and 0.81 or less.
[0011] A fourth embodiment of this disclosure provides a food or pharmaceutical product comprising any one of the magnesium glycinate compounds described in the first to third embodiments.
[0012] A fifth embodiment of this disclosure provides a method for producing food or pharmaceuticals using any one of the magnesium glycinate described in the first to third embodiments.
[0013] A sixth embodiment of the present disclosure provides a magnesium glycinate tablet comprising the magnesium glycinate according to any one of the first to third embodiments.
[0014] A seventh embodiment of the present disclosure provides a magnesium glycinate tablet having a tensile strength of 100 N / cm when compressed at a tableting pressure of 5 kN per tablet 2 to 500 N / cm 2 or less. In the seventh embodiment, the tensile strength of the magnesium glycinate tablet when compressed at a tableting pressure of 5 kN per tablet may be 100 N / cm 2 to 500 N / cm 2 or less.
[0015] An eighth embodiment of the present disclosure provides a method for producing magnesium glycinate, comprising the step of reacting glycine with a magnesium raw material to obtain magnesium glycinate, wherein the magnesium raw material comprises one or more selected from magnesium hydroxide and magnesium oxide.
[0016] A ninth embodiment of the present disclosure provides a method for producing magnesium glycinate, comprising the step of spray-drying a slurry containing glycine and a magnesium raw material to obtain magnesium glycinate, wherein the magnesium raw material comprises one or more selected from magnesium hydroxide and magnesium oxide, the solid content concentration of the slurry is 9.1 mass% or more and 41.7 mass% or less, and the temperature of the slurry immediately before spraying is 20°C or more and 90°C or less.
[0017] In a tenth embodiment of the present disclosure, in any one of the eighth embodiment or the ninth embodiment, the magnesium raw material may comprise magnesium hydroxide.
[0018] The eleventh embodiment of the present disclosure is the one according to any one of the eighth to tenth embodiments, wherein the total content of iron and manganese in the magnesium raw material may be 0 mass ppm or more and 270 mass ppm or less relative to the total amount of the magnesium raw material.
[0019] In the twelfth embodiment of the present disclosure, in any one of the eighth to eleventh embodiments, the magnesium raw material may further contain magnesium hydroxide and magnesium oxide. The content of magnesium hydroxide in the magnesium raw material may be 20 mass% or more. [Effects of the Invention]
[0020] The magnesium glycinate of the present disclosure has good compression moldability. [Brief Description of the Drawings]
[0021] [Figure 1] Figure 1 is the powder X-ray diffraction spectrum of magnesium glycinate in Test Example 1-10, Test Example 1-17 and Comparative Example 1. [Figure 2] Figure 2 is the powder X-ray diffraction spectrum of magnesium hydroxide. [Figure 3] Figure 3 is the powder X-ray diffraction spectrum of magnesium oxide, and magnesium glycinate in Test Example 1-19 and Test Example 1-20. [Figure 4] Figure 4 is the thermogravimetric analysis curve of magnesium hydroxide, glycine, Test Example 1-10, Test Example 1-17 and Comparative Example 1. [Figure 5] Figure 5 is a diagram showing an example of peak fitting when calculating the degree of crystallinity. [Mode for Carrying Out the Invention]
[0022] The present disclosure relates to magnesium glycinate. In addition, in the present specification, unless otherwise specified, various numerical ranges mean ranges including the upper and lower limit values thereof.
[0023] Magnesium glycinate, as a compound, is thought to have a structure in which two ligands, each consisting of a magnesium atom and a glycine atom from which one hydrogen atom has been removed, are bonded. Magnesium glycinate can exist in amorphous or crystalline form.
[0024] In this disclosure, when we refer to magnesium glycinate simply, we are not limited to magnesium glycinate as a compound, but also include materials containing components other than magnesium glycinate. In such materials, the form of magnesium glycinate is not particularly limited and may include either crystalline or amorphous forms.
[0025] (First embodiment: Magnesium glycinate) In the magnesium glycinate of this disclosure, when S1 is the area of amorphous peaks in the X-ray powder diffraction (XRD) spectrum where the maximum value is in the range of 20°≦2θ≦30° and the full width at half maximum (hereinafter also referred to as "FWHM") is 2° or more, and S2 is the area obtained by subtracting the sum of the areas of peaks attributed to magnesium hydroxide from the sum of the areas of crystalline peaks where the maximum value is in the range of 5°≦2θ≦70° and the full width at half maximum is less than 1°, the crystallinity expressed as S2 / (S1+S2) (hereinafter also simply referred to as "crystallinity") is between 0 and 0.9.
[0026] The magnesium glycinate disclosed herein has good compressibility. Therefore, it is expected that using the magnesium glycinate disclosed herein will reduce the use of additives required for molding and make it possible to obtain tablets with a high concentration of magnesium glycinate. Furthermore, the tablets obtained from the magnesium glycinate disclosed herein have good tensile strength. Therefore, it is expected that it will be possible to obtain tablets by compressing magnesium glycinate and distribute the tablets while maintaining their stability. As a result, it will be possible to provide magnesium glycinate, which is conventionally sold as a hard capsule formulation, as a tablet, and it is expected that the burden on users in terms of the number and size of tablets to be taken will be reduced. This disclosure should not be interpreted as being limited to any particular theory, but the reasons why the magnesium glycinate disclosed herein can produce the above effects are thought to be as follows.
[0027] In other words, the magnesium glycinate of this disclosure is thought to have a low degree of crystallinity and a high proportion of amorphous material. As a result, it is thought that it can be deformed more easily than crystalline material when subjected to compressive stress, resulting in good compressible properties.
[0028] The degree of crystallinity of magnesium glycinate is preferably 0 to 0.9, more preferably 0 to 0.87, and even more preferably 0 to 0.81. Having a degree of crystallinity within this range results in better compression moldability. In a preferred embodiment, the degree of crystallinity of magnesium glycinate is preferably 0 to 0.95, more preferably 0.5 to 0.93, and even more preferably 0.7 to 0.9.
[0029] The amorphous peak is considered to be a peak attributed to amorphous magnesium glycinate. The 2θ range in which the maximum value of the amorphous peak exists is 20° to 30° in the X-ray powder diffraction (XRD) spectrum, preferably 20.5° to 29°, and more preferably 21° to 28°.
[0030] The full width at half maximum (FWHM) of the amorphous peak is 2° or more in the X-ray powder diffraction (XRD) spectrum, preferably 2.2° or more, more preferably 2.4° or more, and although there is no upper limit, it is preferably 20° or less, more preferably 18° or less, and even more preferably 16° or less.
[0031] The crystal peak is thought to originate from the crystalline component. Examples of such crystalline components include magnesium glycinate crystals and other crystals such as magnesium hydroxide. The range of 2θ in which the maximum value of the crystal peak exists is 5° to 70° in the X-ray powder diffraction (XRD) spectrum, preferably 10° to 50°, and more preferably 12° to 45°.
[0032] The full width at half maximum (FWHM) of the crystal peak is greater than 0° and less than 1° in the X-ray powder diffraction (XRD) spectrum, more preferably greater than 0° and 0.8° or less, even more preferably greater than 0° and 0.6° or less, with no lower limit, but greater than 0°, preferably 0.05° or more, and even more preferably 0.08° or more.
[0033] In this disclosure, the XRD spectrum of magnesium glycinate can be measured by powder X-ray diffraction. In such powder X-ray diffraction measurements, CuKα rays (λ=1.5418 Å) are used as the X-ray source, and measurements can be performed with an acceleration voltage of 45 kV and an angular step of 0.026°.
[0034] When the magnesium glycinate of this disclosure contains glycine crystals, it is preferable that the magnesium glycinate crystals contain α-type glycine crystals. Since α-type is a metastable crystal and chelates more easily than stable γ-type crystals, it is considered that the overall crystallinity of magnesium glycinate can be controlled to be higher. α-type crystals may, for example, have one or more (preferably all) peaks in the X-ray powder diffraction (XRD) spectrum where 2θ is preferably selected from the ranges of 18.8° to 19.2°, 23.7° to 24.1°, and 35.1° to 35.5°. γ-type crystals may, for example, have one or more (preferably all) peaks in the X-ray powder diffraction (XRD) spectrum where 2θ is preferably selected from the ranges of 21.5° to 21.9°, 25.0° to 25.4°, and 35.7° to 35.9°.
[0035] In thermogravimetric analysis, the magnesium glycinate of this disclosure may have a weight loss rate of preferably 0% to 40% by mass, more preferably 10% to 40% by mass, and even more preferably 20% to 40% by mass, relative to the weight at 50°C, when measured at 400°C. The weight loss in the range of 50°C to 400°C is thought to be due to the combustion of free water, hydration water, glycine present as an impurity in the magnesium glycinate, and the combustion of magnesium glycinate as a compound. In this disclosure, thermogravimetric analysis can be performed under a nitrogen atmosphere in the range of 30°C to 600°C with a heating rate of 10°C / min.
[0036] The content of magnesium glycinate as a compound in the magnesium glycinate of the present disclosure is preferably 85% by mass or more and 100% by mass or less, more preferably 87% by mass or more and 99% by mass or less, and even more preferably 90% by mass or more and 98% by mass or less, based on the total amount of magnesium glycinate of the present disclosure (magnesium glycinate as a material) excluding water.
[0037] The content of magnesium glycinate as a compound in magnesium glycinate can be calculated based on thermogravimetric analysis. Specifically, Total weight [g] - Moisture content [g] - Glycine content [g] - [(Glycine content [g] / Molecular weight of glycine (75.07) [g / mol]) × Formula weight of magnesium hydroxide (58.32) [g / mol] × 0.5] It can be calculated as follows, and the content is expressed as a percentage of the value obtained by subtracting the amount of water from the total weight (total weight - amount of water). Here, the amount of hydration water can be measured as the difference between the weight at 180°C and the weight at 50°C when thermogravimetric analysis is performed on magnesium glycinate at a heating rate of 10°C / min, and the amount of residual glycine can similarly be measured as the difference between the weight at 200°C and the weight at 280°C.
[0038] The magnesium glycinate of this disclosure may contain components other than magnesium glycinate as a compound. Examples of such components include magnesium hydroxide. The magnesium hydroxide content in the magnesium glycinate of this disclosure is preferably 0% by mass or more and 10% by mass or less, more preferably 0% by mass or more and 5% by mass or less, and even more preferably 0% by mass or more and 3% by mass or less, based on the total amount of magnesium glycinate of this disclosure (magnesium glycinate as a material).
[0039] The magnesium hydroxide content in the magnesium glycinate (magnesium glycinate as a material) of this disclosure can be quantitatively analyzed by X-ray powder diffraction measurement using the least squares method, RIR (Reference Intensity Ratio) method, etc. Alternatively, theoretically, since glycine and magnesium hydroxide chelate in a molar ratio of 2:1, the remaining amount of magnesium hydroxide is half the amount of the remaining glycine ((remaining amount of glycine [g] / molecular weight of glycine (75.07) [g / mol]) × formula weight of magnesium hydroxide (58.32) [g / mol] × 0.5). The content can be calculated based on this remaining amount of magnesium hydroxide.
[0040] The magnesium glycinate of this disclosure may be in powder, particulate, granular, or the like. The average particle size of the magnesium glycinate of this disclosure is preferably 1 μm to 350 μm, more preferably 10 μm to 300 μm, even more preferably 20 μm to 250 μm, and even more preferably 30 μm to 100 μm. In this disclosure, the average particle size refers to the volume-based median diameter (D50) and can be measured by laser diffraction-scattering.
[0041] (Second embodiment: Method for producing magnesium glycinate) The magnesium glycinate of this disclosure can be produced by a manufacturing method that includes a step of reacting glycine with a magnesium raw material to obtain magnesium glycinate. The above magnesium raw material includes one or more selected from magnesium hydroxide and magnesium oxide.
[0042] According to the above manufacturing method, magnesium glycinate with good compressible properties can be produced. This disclosure should not be interpreted as being limited to any particular theory, but the reason why such an effect is obtained by the manufacturing method of this disclosure is thought to be as follows: When glycine and magnesium raw materials are reacted, the rate of the chelation reaction slows down, and as a result, crystal growth is inhibited, so amorphous material is more likely to be formed instead of crystals. As a result, it is thought that magnesium glycinate with good compressible properties is more easily obtained.
[0043] The amount of glycine is preferably 0.32 parts by mass to 7.7 parts by mass, more preferably 0.64 parts by mass to 6.4 parts by mass, and even more preferably 1.3 parts by mass to 5.1 parts by mass, per 1 part by mass of magnesium raw material. By having the amount of glycine within the above range relative to the amount of magnesium raw material, the reaction efficiency is increased, and it is easy to further increase the magnesium concentration in the resulting magnesium glycinate.
[0044] The amount of glycine is preferably 0.32 parts by mass to 7.7 parts by mass, more preferably 0.64 parts by mass to 6.4 parts by mass, and even more preferably 1.3 parts by mass to 5.1 parts by mass, per 1 part by mass of magnesium hydroxide. By having the amount of glycine within the above range relative to the amount of magnesium hydroxide, the reaction efficiency is increased, and it is easy to further increase the magnesium concentration in the resulting magnesium glycinate.
[0045] The amount of glycine is preferably 1.4 moles to 2.6 moles, more preferably 1.6 moles to 2.4 moles, and even more preferably 1.8 moles to 2.2 moles, per mole of magnesium contained in the magnesium raw material.
[0046] Glycine may contain glycine crystals. Examples of glycine crystals include α-type, β-type, and γ-type. It is preferable that the glycine crystals contain α-type glycine crystals. Since α-type is a metastable crystal and chelates more easily than the stable γ-type crystal, it is thought that the crystallinity of the resulting magnesium glycinate can be controlled to increase.
[0047] Magnesium raw materials are typically inorganic compounds containing magnesium, and include one or more selected from magnesium hydroxide and magnesium oxide.
[0048] In one embodiment, the magnesium raw material preferably contains magnesium hydroxide. The magnesium hydroxide content is preferably 27% by mass or more and 100% by mass or less, more preferably 60% by mass or more and 100% by mass or less, and even more preferably 80% by mass or more and 100% by mass or less, relative to the magnesium raw material.
[0049] In another embodiment, the magnesium raw material preferably contains magnesium oxide. The magnesium oxide content is preferably 27% to 100% by mass, more preferably 60% to 100% by mass, and even more preferably 80% to 100% by mass, relative to the magnesium raw material.
[0050] In yet another embodiment, the magnesium raw material preferably includes magnesium hydroxide and magnesium oxide. When magnesium oxide is included, the magnesium hydroxide content is preferably 20% by mass or more, more preferably 27% by mass or more and 100% by mass or less, even more preferably 60% by mass or more and 100% by mass or less, and even more preferably 65% by mass or more and 100% by mass or less, relative to the magnesium raw material.
[0051] The magnesium oxide content in the magnesium raw material is preferably 0 to 270 parts by mass, more preferably 0 to 150 parts by mass, and even more preferably 0 to 100 parts by mass, per 100 parts by mass of magnesium hydroxide contained in the magnesium raw material.
[0052] The molar ratio of magnesium oxide to magnesium hydroxide (magnesium oxide:magnesium hydroxide) in the magnesium raw material is preferably 0:10 to 8:2, more preferably 0:10 to 7:4, and even more preferably 0:10 to 6:4. Reducing the proportion of magnesium oxide tends to lower the degree of crystallinity, while increasing the proportion of magnesium oxide tends to increase the degree of crystallinity.
[0053] It is preferable that the magnesium raw material has a low heavy metal concentration. A low heavy metal concentration in the magnesium raw material is thought to suppress the formation of magnesium glycinate crystal nuclei, making it easier to obtain magnesium glycinate with low crystallinity.
[0054] Examples of the heavy metals mentioned above include, but are not limited to, chromium, manganese, iron, cobalt, nickel, copper, zinc, molybdenum, ruthenium, rhodium, palladium, silver, cadmium, and tin.
[0055] The iron content in the magnesium raw material is preferably 0 ppm to 200 ppm by mass, more preferably 0 ppm to 150 ppm by mass, and even more preferably 0 ppm to 100 ppm by mass, relative to the total amount of magnesium raw materials. Having the iron content in the magnesium raw material within this range suggests a low concentration of heavy metals in the magnesium raw material, making it easy to suppress the crystallinity of the resulting magnesium glycinate.
[0056] The manganese content in the magnesium raw material is preferably 0 ppm to 70 ppm by mass, more preferably 0 ppm to 50 ppm by mass, and even more preferably 0 ppm to 30 ppm by mass, relative to the total amount of magnesium raw materials. Having the manganese content in the magnesium raw material within this range suggests a low concentration of heavy metals in the magnesium raw material, making it easy to suppress the crystallinity of the resulting magnesium glycinate.
[0057] The total content of iron and manganese in the magnesium raw material is preferably 0 ppm to 270 ppm by mass, more preferably 0 ppm to 200 ppm by mass, and even more preferably 0 ppm to 130 ppm by mass, relative to the total content of the magnesium raw material. Because the iron and manganese content in the magnesium raw material is within this range, the concentration of heavy metals in the magnesium raw material is presumed to be low, making it easy to suppress the crystallinity of the resulting magnesium glycinate.
[0058] The iron content in magnesium hydroxide is preferably 0 ppm to 100 ppm by mass, more preferably 0 ppm to 50 ppm by mass, and even more preferably 0 ppm to 25 ppm by mass, relative to the total amount of magnesium hydroxide. Because the iron content in magnesium hydroxide is within this range, the concentration of heavy metals in the magnesium hydroxide is presumed to be low, making it easy to suppress the crystallinity of the resulting magnesium glycinate.
[0059] The manganese content in magnesium hydroxide is preferably 0 ppm to 20 ppm by mass, more preferably 0 ppm to 10 ppm by mass, and even more preferably 0 ppm to 5 ppm by mass, relative to the total amount of magnesium hydroxide. Because the manganese content in magnesium hydroxide is within this range, the concentration of heavy metals in the magnesium hydroxide is presumed to be low, making it easy to suppress the crystallinity of the resulting magnesium glycinate.
[0060] The total content of iron and manganese in magnesium hydroxide is preferably 0 ppm to 120 ppm by mass, more preferably 0 ppm to 60 ppm by mass, and even more preferably 0 ppm to 30 ppm by mass, relative to the total content of magnesium hydroxide. Because the iron and manganese content in magnesium hydroxide is within this range, the concentration of heavy metals in the magnesium hydroxide is presumed to be low, making it easy to suppress the crystallinity of the resulting magnesium glycinate.
[0061] The iron content in magnesium oxide is preferably 0 ppm to 200 ppm by mass, more preferably 0 ppm to 100 ppm by mass, and even more preferably 0 ppm to 50 ppm by mass, relative to the total amount of magnesium oxide. Because the iron content in magnesium oxide is within this range, the concentration of heavy metals in the magnesium oxide is presumed to be low, making it easy to suppress the crystallinity of the resulting magnesium glycinate.
[0062] The manganese content in magnesium oxide is preferably 0 ppm to 40 ppm by mass, more preferably 0 ppm to 20 ppm by mass, and even more preferably 0 ppm to 10 ppm by mass, relative to the total amount of magnesium oxide. Because the manganese content in magnesium oxide is within this range, the concentration of heavy metals in the magnesium oxide is presumed to be low, making it easy to suppress the crystallinity of the resulting magnesium glycinate.
[0063] The total content of iron and manganese in magnesium oxide is preferably 0 ppm to 240 ppm by mass, more preferably 0 ppm to 120 ppm by mass, and even more preferably 0 ppm to 60 ppm by mass, relative to the total content of magnesium oxide. Because the iron and manganese content in magnesium oxide is within this range, the concentration of heavy metals in the magnesium oxide is presumed to be low, making it easy to suppress the crystallinity of the resulting magnesium glycinate.
[0064] In this disclosure, the heavy metal content can be measured by radio frequency inductively coupled plasma (ICP) emission spectroscopy.
[0065] The reaction between glycine and the magnesium raw material is preferably carried out by spray-drying the slurry containing the glycine and magnesium raw material. It is believed that spray-drying can suppress crystallization after the chelation reaction between glycine and the magnesium raw material, making it easier to generate amorphous material.
[0066] The magnesium raw material content is preferably 20% to 40% by mass, more preferably 20% to 30% by mass, and even more preferably 25% to 30% by mass, relative to the solid content in the slurry.
[0067] The iron content in the slurry is preferably 0 ppm to 20 ppm by mass, more preferably 0 ppm to 15 ppm by mass, and even more preferably 0 ppm to 10 ppm by mass, relative to the total slurry content. Because the iron content in the slurry is within this range, the concentration of heavy metals in the slurry is presumed to be low, making it easy to suppress the crystallinity of the resulting magnesium glycinate.
[0068] The manganese content in the slurry is preferably 0 ppm to 10 ppm by mass, more preferably 0 ppm to 8 ppm by mass, and even more preferably 0 ppm to 6 ppm by mass, relative to the total slurry content. Having the manganese content in the slurry within this range suggests that the concentration of heavy metals in the slurry is also low, making it easier to suppress the crystallinity of the resulting magnesium glycinate.
[0069] The total content of iron and manganese in the slurry is preferably 0 ppm to 30 ppm by mass, more preferably 0 ppm to 23 ppm by mass, and even more preferably 0 ppm to 16 ppm by mass, relative to the total content of the slurry. Since the iron and manganese content in the slurry is within this range, the concentration of heavy metals in the slurry is presumed to be low, making it easy to suppress the crystallinity of the resulting magnesium glycinate.
[0070] The solid content concentration in the slurry is preferably 9.1% by mass or more and 41.7% by mass or less, more preferably 9.1% by mass or more and 35% by mass or less, and even more preferably 9.1% by mass or more and 30% by mass or less.
[0071] In this disclosure, the solid content of the mixture means the residue after heating the mixture at 105°C for 4 hours, and the solid content concentration means the value obtained by dividing the total mass of the residue by the total mass of the mixture subjected to heating.
[0072] The dispersion medium in the slurry preferably contains water. The water content is preferably 50% to 100% by mass, more preferably 90% to 100% by mass, and even more preferably 95% to 100% by mass, relative to the dispersion medium. The dispersion medium may also contain other solvents. The dispersion medium may contain alcohols such as methanol, ethanol, and isopropanol.
[0073] The slurry can be produced by mixing glycine with magnesium raw materials and a dispersion medium.
[0074] The mixing time between glycine, magnesium raw material, and dispersion medium is preferably 10 minutes to 10 hours, more preferably 30 minutes to 6 hours, and even more preferably 1 hour to 3 hours. Mixing is thought to improve the uniformity of the slurry. Furthermore, it is thought that the shorter the mixing time, the more the formation of substances that can act as crystal nuclei is suppressed, and the easier it is to suppress the crystallinity of the resulting magnesium glycinate.
[0075] The mixing temperature is preferably 5°C to 80°C, more preferably 10°C to 70°C, even more preferably 15°C to 50°C, and even more preferably 20°C to 45°C. By setting the mixing temperature within the above range, the dissolution of the raw materials in water is suppressed, the formation of substances that can act as crystal nuclei is suppressed, and it is considered easy to suppress the crystallinity of the resulting magnesium glycinate.
[0076] Spray drying can typically be carried out using a spray dryer. While the conditions for spray drying are not limited, the slurry temperature immediately before spraying is preferably 15°C to 95°C, more preferably 20°C to 90°C, even more preferably 40°C to 90°C, and even more preferably 50°C to 90°C. It is believed that increasing the slurry temperature immediately before spraying can suppress the formation of magnesium glycinate crystal nuclei, making it easier to suppress the crystallinity of the resulting magnesium glycinate. In a preferred embodiment, the slurry temperature immediately before spraying is preferably 15°C to 95°C, more preferably 20°C to 80°C, even more preferably 20°C to 60°C, and even more preferably 20°C to 45°C. Lowering the temperature immediately before spraying results in good reproducibility.
[0077] The resulting magnesium glycinate may be subjected to drying and / or grinding.
[0078] The inlet drying temperature during the above drying process is not limited; it is sufficient if the outlet temperature reaches an appropriate value. The outlet temperature is preferably 50°C to 120°C, more preferably 60°C to 110°C, and even more preferably 80°C to 110°C. The drying time depends on the amount of liquid sprayed and is not particularly limited as long as the product does not adhere significantly to the inside of the machine, making powder recovery difficult.
[0079] The above drying can be carried out using a spray dryer, hot air dryer, microwave dryer, rotary dryer, etc.
[0080] The above grinding can be carried out so that the average particle size of magnesium glycinate is preferably 1 μm to 350 μm, more preferably 10 μm to 300 μm, even more preferably 20 μm to 250 μm, and even more preferably 30 μm to 100 μm.
[0081] The above grinding can be carried out using a fine grinding machine such as a roller mill, jet mill, high-speed rotary grinder, or container-driven mill.
[0082] The magnesium glycinate of this disclosure may be produced by the above-described manufacturing method, but is not limited to that produced by the above-described manufacturing method.
[0083] (Third embodiment: Magnesium glycinate tablets) Magnesium glycinate tablets are also included in the technical scope of this disclosure. In one embodiment, the magnesium glycinate tablets of this disclosure contain the magnesium glycinate of this disclosure. In another embodiment, the magnesium glycinate tablets of this disclosure have a tensile strength of 100 N / cm when compressed with a tableting pressure of 5 kN per tablet. 2 More than 500N / cm 2 The following applies:
[0084] The magnesium glycinate disclosed herein is expected to have good compression moldability, making it possible to obtain tablets with a high concentration of magnesium glycinate. Furthermore, the magnesium glycinate tablets disclosed herein are expected to have high tensile strength, making it possible to maintain the stability of the tablets.
[0085] The content of magnesium glycinate as a compound in magnesium glycinate tablets is preferably 20% by mass or more and 95% by mass or less, more preferably 50% by mass or more and 95% by mass or less, and even more preferably 66.7% by mass or more and 90% by mass or less.
[0086] The magnesium glycinate content in the magnesium glycinate tablets of this disclosure is preferably 0.1% by mass or more and 90% by mass or less, more preferably 10% by mass or more and 80% by mass or less, and even more preferably 20% by mass or more and 70% by mass or less.
[0087] Magnesium glycinate tablets may contain, in addition to magnesium glycinate, internal or external additives such as disintegrants including low-substituted hydroxypropyl cellulose, agar, croscarmellose sodium, partially pregelatinized starch, potato starch, corn starch, carmellose calcium, crospovidone, and carboxystarch sodium; binders such as crystalline cellulose, carboxypropyl cellulose, carboxypropyl methylcellulose, and pullulan; lubricants such as sucrose fatty acid esters, glycerin fatty acid esters, stearyl fumarate sodium, talc, stearic acid, and their salts (Mg,Ca salts); fluidity improvers such as fine silicon dioxide and calcined seashell calcium; sweeteners such as aspartame, acesulfame potassium, and sucralose; and excipients such as calcium hydrogen phosphate, sugar alcohols, monosaccharides, disaccharides, oligosaccharides, cellulose, cellulose derivatives, starch, starch derivatives, and starch hydrolysates. Furthermore, magnesium glycinate tablets may further contain other additives such as amino acids or their salts, yeast extracts, vitamins, minerals, functional ingredients, various polyphenols, binders, colorants, pH adjusters, buffers, and antioxidants.
[0088] The tensile strength of the magnesium glycinate tablet when compressed at a tableting pressure of 5 kN per tablet is preferably 100 N / cm 2 to 500 N / cm 2 , more preferably 100 N / cm 2 to 400 N / cm 2 , still more preferably 100 N / cm 2 to 350 N / cm 2 or less. It is considered that when the tensile strength of the magnesium glycinate tablet falls within such a range, it becomes easy to maintain the tablet in a stable state.
[0089] The shape of the magnesium glycinate tablet is not particularly limited, and may be, for example, standard round, double-layer round, sugar-coated round, beveled edge round, beveled flat, rounded flat, triangular, oblong, or hexagonal.
[0090] The size of the magnesium glycinate tablet is not particularly limited. In one aspect, the diameter of the magnesium glycinate tablet is preferably 5 mm to 14 mm, more preferably 5 mm to 10 mm, and still more preferably 5 mm to 9 mm. The thickness of the magnesium glycinate tablet is preferably 2 mm to 7 mm, 3 mm to 6.5 mm, or 3.5 mm to 6.5 mm. The weight per magnesium glycinate tablet is preferably 50 mg to 1,000 mg, more preferably 70 mg to 800 mg, and still more preferably 90 mg to 600 mg.
[0091] The magnesium glycinate tablet can be produced by a production method comprising the steps of: mixing magnesium glycinate, and an internal additive, an external additive and other additives used as necessary to obtain a mixed powder; and tableting the obtained mixed powder to obtain the magnesium glycinate tablet. When tableting the mixed powder, the mixed powder may be dispersed in a dispersion medium such as water and sprayed, or the mixed powder may be granulated. In addition, a coating for the purpose of coloring the appearance to enhance commercial value, or imparting taste or odor may be added in a subsequent step.
[0092] The average particle size of the mixed powder is preferably 100 μm to 850 μm, more preferably 150 μm to 500 μm, and even more preferably 150 μm to 300 μm.
[0093] The method of tableting is not limited, but typically it can be carried out using a tablet press. For example, the tableting pressure per tablet is not limited, but is preferably 2kN to 20kN, more preferably 3kN to 18kN, and even more preferably 4kN to 16kN. Higher pressure results in higher hardness, but it also increases the load on the punch and the machine itself, leading to repair costs, so it is preferable to use the lowest possible pressure.
[0094] (Fourth embodiment: Pharmaceuticals or food and beverages) The magnesium glycinate of this disclosure can be suitably used in a variety of applications. Such applications include food and beverages and pharmaceuticals, and this disclosure also includes food and beverages and pharmaceuticals that contain magnesium glycinate. Such food and beverages and pharmaceuticals can be manufactured using the magnesium glycinate of this disclosure.
[0095] Magnesium glycinate is thought to replenish magnesium in the body upon absorption. Magnesium intake is also expected to have effects such as increasing melatonin levels in the brain, promoting relaxation, improving sleep, and stabilizing blood sugar levels. Because magnesium glycinate is highly absorbable and has suppressed laxative side effects, it is preferable for use in foods, beverages, and pharmaceuticals.
[0096] In this disclosure, "food and beverages" refers to all food and beverages, including general foods such as health foods; foods with functional claims; health functional foods such as foods for specified health uses and foods with nutritional function; and supplements. Furthermore, "food and beverages" is not limited to those administered to humans, but also includes livestock feed, pet food, etc., administered to animals.
[0097] The form of food and beverages is not particularly limited and may be solid, semi-solid, or liquid. Specific forms include tablets, pills, capsules, liquids, pastes, syrups, powders, granules, gummies, gels, and the like.
[0098] Furthermore, the "pharmaceutical" can be administered to the target in any form, and may be administered orally or parenterally. Preferably, it can be administered orally.
[0099] Such medicines can be used to treat diseases such as magnesium deficiency, insomnia, and depression, as well as the various symptoms associated with them.
[0100] The dosage forms of pharmaceuticals are not particularly limited and include oral solid preparations such as tablets, granules, powders, and capsules; oral liquid preparations such as oral solutions and syrups; and parenteral liquid preparations such as injections.
[0101] When magnesium glycinate of this disclosure is used in food and beverages, it may further contain additives such as excipients, coating agents, binders, bulking agents, disintegrants, surfactants, lubricants, diluents, dispersants, buffers, osmotic pressure adjusters, pH adjusters, emulsifiers, preservatives, stabilizers, antioxidants, colorants, UV absorbers, humectants, thickeners, activity enhancers, anti-inflammatory agents, bactericides, flavoring agents, and odor-masking agents.
[0102] Foods, beverages, or pharmaceuticals containing magnesium glycinate as disclosed herein can be used by administering them to the subject.
[0103] The magnesium glycinate disclosed herein exhibits good compressive deformability. Furthermore, tablets obtained from the magnesium glycinate disclosed herein have good tensile strength. Therefore, it is expected that it will be possible to obtain tablets by compressing magnesium glycinate and maintain the stability of said tablets. For this reason, the magnesium glycinate disclosed herein is preferably used in foods and beverages and pharmaceuticals. Furthermore, the magnesium glycinate disclosed herein is preferably used in the manufacturing methods of foods and beverages and pharmaceuticals. [Examples]
[0104] The present disclosure will be further illustrated by the following embodiments, but will not be limited thereto.
[0105] (Test Example 1-1) 18.0 g of glycine (special grade, Fujifilm Wako Pure Chemical Industries, γ-type crystal) and 7.0 g of magnesium hydroxide (iron content 86.7 ppm by mass, manganese content 14.8 ppm by mass, the same applies hereafter) were weighed and simultaneously added to 50 mL of deionized water. The mixture was then stirred in a water bath at room temperature (22-26°C) for 18 hours (As One, VOLTEGA, Power Stirrer VPS-160BD). The resulting slurry was spray-dried at room temperature (22-26°C) while being stirred using a spray dryer (YAMATO Kagaku, Palvis Mini Spray GB210A), and 3.2 g of magnesium glycinate powder was recovered. During spray drying, the inlet temperature was 180°C, the outlet temperature was 78-82°C, and the air flow rate was 0.4-0.5 m³. 3 The condition was set to / minutes.
[0106] (Test Example 1-2) Except for adding glycine to deionized water and stirring for 1 hour, followed by the addition of magnesium hydroxide, the mixture was powdered in the same manner as in Test Example 1-1 to obtain 3.5 g of magnesium glycinate powder.
[0107] (Test Examples 1-3) Except for using magnesium hydroxide alone, the mixture consisted of 0.5 g of magnesium oxide (iron content 176 ppm by mass, manganese content 27.7 ppm by mass; the same applies hereafter unless otherwise specified) and 6.5 g of magnesium hydroxide, which were powdered in the same manner as in Test Example 1-1 to obtain 5.5 g of magnesium glycinate powder.
[0108] (Test Examples 1-4) Except for using 1 g of magnesium oxide and 6 g of magnesium hydroxide instead of magnesium hydroxide alone, the powder was prepared in the same manner as in Test Example 1-2, yielding 8.0 g of magnesium glycinate powder.
[0109] (Test Examples 1-5) The powder was prepared in the same manner as in Test Example 1-2, except that instead of magnesium hydroxide alone, 1.6 g of magnesium oxide and 5.4 g of magnesium hydroxide were used, yielding 5.6 g of magnesium glycinate powder.
[0110] (Test Examples 1-6) The powder was prepared in the same manner as in Test Example 1-2, except that instead of magnesium hydroxide alone, 2.2 g of magnesium oxide and 4.8 g of magnesium hydroxide were used, yielding 6.4 g of magnesium glycinate powder.
[0111] (Test Examples 1-7) The powder was prepared in the same manner as in Test Example 1-2, except that instead of magnesium hydroxide alone, 2.9 g of magnesium oxide and 4.1 g of magnesium hydroxide were used, yielding 6.0 g of magnesium glycinate powder.
[0112] (Test Examples 1-8) The powder was prepared in the same manner as in Test Example 1-2, except that instead of magnesium hydroxide alone, 3.6 g of magnesium oxide and 3.4 g of magnesium hydroxide were used, yielding 5.9 g of magnesium glycinate powder.
[0113] (Test Examples 1-9) The powder was prepared in the same manner as in Test Example 1-2, except that instead of magnesium hydroxide alone, 4.3 g of magnesium oxide and 2.7 g of magnesium hydroxide were used, yielding 7.1 g of magnesium glycinate powder.
[0114] (Test Examples 1-10) Except for using 5.1g of magnesium oxide and 1.9g of magnesium hydroxide instead of magnesium hydroxide alone, the mixture was powdered in the same manner as in Test Example 1-2 to obtain 2.6g of magnesium glycinate powder.
[0115] (Test example 1-11) The procedure was the same as in Test Example 1-2, except that the volume of deionized water was changed to 75 mL, and 6.1 g of magnesium glycinate powder was obtained.
[0116] (Test Examples 1-12) The procedure was the same as in Test Example 1-2, except that the volume of deionized water was changed to 125 mL, and 9.2 g of magnesium glycinate powder was obtained.
[0117] (Test Examples 1-13) The procedure was the same as in Test Example 1-2, except that the volume of deionized water was changed to 250 mL, and 11.0 g of magnesium glycinate powder was obtained.
[0118] (Test Examples 1-14) The procedure was the same as in Test Examples 1-6, except that the volume of deionized water was changed to 35 mL, and 5.8 g of magnesium glycinate powder was obtained.
[0119] (Test Examples 1-15) After preparing the slurry solution in the same manner as in Test Examples 1-6, it was heated at 50°C for 1 hour, and while maintaining that temperature, it was powdered in the same manner as in Test Examples 1-6 to obtain 4.2 g of magnesium glycinate powder.
[0120] (Test Examples 1-16) After preparing the slurry solution in the same manner as in Test Examples 1-6, it was heated at 80°C for 1 hour, and while maintaining that temperature, it was powdered in the same manner as in Test Examples 1-6 to obtain 5.4 g of magnesium glycinate powder.
[0121] (Test Examples 1-17) Except for using 75 mL of deionized water, the mixture was powdered in the same manner as in Test Examples 1-16 to obtain 5.6 g of magnesium glycinate powder.
[0122] (Test Examples 1-18) The pulverization process was carried out in the same manner as in Test Examples 1-17, except that the outlet temperature during spray drying was set to 98-102°C, to obtain 6.1 g of magnesium glycinate powder.
[0123] (Test Examples 1-19) 19.71 g of glycine was added to deionized water and stirred for 30 minutes. Then, 5.29 g of magnesium oxide (iron content: 91 ppm by mass, manganese content: 31 ppm by mass) was added instead of magnesium hydroxide. The mixture was powdered in the same manner as in Test Example 1-2, yielding 6.5 g of magnesium glycinate powder.
[0124] (Test Examples 1-20) Except for using magnesium oxide (iron content: 177 ppm by mass, manganese content: 62 ppm by mass) as the magnesium oxide, the mixture was powdered in the same manner as in Test Example 1-19 to obtain 7.2 g of magnesium glycinate powder.
[0125] (Test Example 1-21) As magnesium oxide, magnesium oxide (iron content: 176 ppm by mass, manganese content: 27.7 ppm by mass) was used, and the powdering process was carried out in the same manner as in Test Example 1-19, except that the stirring time after adding the magnesium oxide was 6 hours, to obtain 8.2 g of magnesium glycinate powder.
[0126] (Test example 1-22) 50 mL of deionized water was heated to 80°C, and 19.71 g of α-type glycine crystals (Glycine G, Kobe Chemical) was added and stirred for 30 minutes. Then, magnesium oxide (iron content: 5 ppm by mass, manganese content: 0 ppm by mass) was added and mixed for 2 hours. The reaction slurry was then cooled to below 40°C and powdered in the same manner as in Test Example 1-2 to obtain 6.4 g of magnesium glycinate powder.
[0127] (Test example 1-23) Except for using γ-type crystals as glycine and magnesium oxide (iron content: 176 ppm by mass, manganese content: 27.7 ppm by mass) as magnesium oxide, the mixture was powdered in the same manner as in Test Example 1-22 to obtain 6.0 g of magnesium glycinate powder.
[0128] (Comparative Example 1) Except for using 19.7 g of glycine and 5.3 g of magnesium oxide (iron content: 176 ppm by mass, manganese content: 27.7 ppm by mass) instead of magnesium hydroxide, the mixture was powdered in the same manner as in Test Example 1-1 to obtain 2.1 g of magnesium glycinate.
[0129] The following measurements were performed on the powder obtained in the above test example.
[0130] (Powder X-ray diffraction measurement) Measurements were performed using an X-ray diffractometer, EMPYREAN (Malvern Panalytical). The sample was packed tightly into a circular sample holder manufactured by Malvern Panalytical using a sample preparation kit from Malvern Panalytical. The measurement conditions were as follows: X-ray source: CuKα (λ=1.5418Å) Acceleration voltage: 45kV Step: 2θ = 0.026° Scan speed: 0.656514° / s Divergence slit: 0.5000° Scattering slit: 8.0 mm Solar slit: 0.04rad
[0131] HighScore Plus (Malvern Panalytical) was used to analyze the obtained XRD diffraction patterns. Peak detection and peak fitting were performed, and the phase of the peak top and FWHM were calculated from the obtained peaks. The crystallite size was then calculated using the following formula. Note that the FWHM here is not applied to the calculation of crystallinity. D = Kλ / Bcosθ λ = 1.5418 Å K=0.9 B:FWHM θ: Phase of the peak top
[0132] Furthermore, to calculate the degree of crystallinity, the XRD diffraction pattern analysis software JADE(MDI) was used. The XRD diffraction patterns were obtained from data measured using the X-ray diffractometer described above. The diffraction patterns were loaded into JADE, the baseline was set as a quartic equation, and amorphous peaks were defined so that the peaks were set in the diffraction angle range of 20-30°. Peak fitting was performed to obtain the peak position, area, and full width at half maximum for each peak. Referring to the obtained peak areas, the degree of crystallinity CI for each XRD diffraction pattern was calculated from the following formula. A representative example illustrating the calculation principle is shown in Figure 5. CI = S² / (S1 + S²) S1: Area of an amorphous peak with a maximum value in the range 20°≦2θ≦30° and a full width at half maximum of 2° or more. S2: Area obtained by subtracting the sum of the areas of peaks attributed to magnesium hydroxide in the range 5°≦2θ≦70° from the sum of the areas of crystal peaks with a maximum value in the range 5°≦2θ≦70° and a full width at half maximum of less than 1°.
[0133] (Thermogravimetric analysis) Measurements were performed using a thermogravimetric analyzer, STA2500 Regulus (NETZSCH-Geratebau GmbH). The measurement conditions were as follows: Sample amount: 10-11 mg Sample container: Aluminum pan Heating rate: Heats up from 30°C to 600°C at a rate of 10°C / minute. Atmosphere gas: Nitrogen gas (50 mL / min) Control substance: Alumina (10-11 mg)
[0134] (ICP emission spectroscopy) Iron and manganese content were analyzed by ICP emission spectroscopy. Specifically, the sample to be measured was first heated to over 500°C in an electric furnace to incinerate it, and then iron and manganese were extracted in hydrochloric acid. After removing insoluble solids from the extract by filtration, the volume was adjusted using a volumetric flask, and quantitative analysis was performed by ICP emission spectroscopy.
[0135] (Tensile strength measurement) The tablets manufactured in each test example were cylindrical, and the thickness [mm] in the direction of clamping the circular surface was measured using a commercially available general-purpose digital thickness gauge. The hardness of the tablets was measured using a tablet hardness tester (DR. SCHLEUNIGER MODEL 6D TABLET TESTER) with a force applied horizontally to the circular surface, and the hardness [N] was measured, repeating this three times for each test. The obtained values were converted to tensile strength using the following formula. Tensile strength [N / cm 2 ] = 2 × hardness [N] / (π × 0.1 cm × tablet thickness [cm])
[0136] For Test Examples 1-1 to 22 and Comparative Example 1, the following table shows the results for the magnesium raw material, including the molar ratio of magnesium oxide to magnesium hydroxide (MgO:Mg(OH)2), heavy metal content (Fe content, Mn content), slurry concentration and slurry temperature immediately before spraying, the glycine retention rate in the obtained magnesium glycinate, the weight loss rate at 400°C (TG loss rate) relative to the weight at 50°C (based on thermogravimetric analysis), and the degree of crystallinity.
[0137] [Table 1]
[0138] For Test Examples 1-1 to 1-10, no difference was observed in the results when glycine and magnesium hydroxide were added simultaneously or separately. As the proportion of magnesium oxide in the magnesium raw material was increased, a completely amorphous material was obtained (crystallinity: 0.000) at molar ratios (magnesium oxide:magnesium hydroxide) of 0:10, 1:9, and 4:6, while a mixture of dihydrate crystals and amorphous material was obtained at other molar ratios. In particular, the proportion of crystalline material tended to increase in Test Examples 1-7 to 1-10, where the molar ratio (magnesium oxide:magnesium hydroxide) was 5:5 to 8:2, and in Comparative Example 1, where the molar ratio was 10:0.
[0139] In test examples 1-11 to 14, it was shown that the amount of residual glycine tended to decrease as the slurry concentration decreased, and the chelation efficiency increased. On the other hand, regarding the crystallization rate, it was shown that as the slurry concentration increased from 33.3% to 41.7%, the material changed from amorphous to a mixture of dihydrate crystals and amorphous material.
[0140] In Test Examples 1-6 and 15-18, raising the slurry temperature to 80°C immediately before spraying reduced the residual glycine while maintaining the amorphous state, suggesting that the chelation reaction was accelerated. This trend was also accelerated by lowering the slurry concentration and by changing the glycine crystal form from the stable γ-form to the metastable α-form, while maintaining the amorphous state.
[0141] Furthermore, under spraying conditions, increasing the outlet temperature to approximately 100°C applied heat to the resulting powder, reducing the residual glycine content while maintaining a crystallinity of 0. This method of improving chelation efficiency while maintaining an amorphous state has not been reported in previous studies and was discovered for the first time in this experiment.
[0142] In Test Examples 1-19 and 1-20, it was confirmed that when the stirring time after adding the magnesium raw material was 2 hours, the amorphous state was maintained even when the amount of heavy metals contained in the magnesium raw material increased. On the other hand, in Test Example 1-21, when the stirring time after adding the magnesium raw material was 6 hours, it was confirmed that the crystallinity increased compared to Test Example 1-20, even though the amount of heavy metals contained in the magnesium raw material was lower.
[0143] A comparison of Test Examples 1-8 and 1-21 suggests that the higher the magnesium oxide content in the magnesium raw material, the higher the crystallinity of the resulting magnesium glycinate tends to be. This is because magnesium oxide is more reactive with glycine, and the following factors may also be involved. Specifically, during the spray-drying process, the molecules of glycine and the magnesium raw material are instantaneously fixed, resulting in an amorphous state. Therefore, the degree of crystal growth may depend on the presence of crystal nuclei in the slurry subjected to spray drying. Considering these points, it is possible that the crystallinity is higher when magnesium oxide is used as the magnesium raw material because the time to reach saturation solubility is shorter, and crystal nuclei for magnesium glycinate are more easily formed. This is consistent with the fact that in Test Example 1-14, where the slurry concentration is high, saturation solubility is reached and crystal nuclei are more easily formed, resulting in a higher degree of crystallinity of the resulting magnesium glycinate.
[0144] A comparison of test examples 1-22 and 1-23 confirmed that changing the crystalline form of glycine from the stable γ-form to the metastable α-form increased the degree of crystallinity, even when conditions for creating an amorphous state (low heavy metal content and short reaction time) were met. This is thought to be due to the α-form crystalline glycine promoting the chelation reaction and reducing unreacted products, thereby increasing the degree of crystallinity. Furthermore, the increased chelation likely resulted in a lower amount of residual glycine.
[0145] (Examples 2-1, 2, 3, Comparative Example 2) Examples 2-1, 2-2, and 2-3 were created using the following formulations of magnesium glycinate, as shown in Test Example 1-17 (crystallinity: 0.000), Test Example 1-4 (crystallinity: 0.325), and Test Example 1-10 (crystallinity: 0.810). Comparative Example 2 (crystallinity: 1.000) was created using a commercially available non-amorphous dihydrate crystalline raw material (Actylis, Magnesium Bisglycinate). In this case, crystalline cellulose (Asahi Kasei Ceolus UF-F702), fine silicon dioxide (Fuji Silicia Silope 720), and calcium stearate (Taihei Chemical) were used, and the formulations shown in the table below were used. The total weight of each raw material was 4.5g, and the tablets were compressed the following day. In the above-mentioned commercially available non-amorphous dihydrate crystalline raw material (Actylis, Magnesium Bisglycinate), thermogravimetric analysis showed a weight loss of 45.8% by mass at 400°C compared to the weight at 50°C.
[0146] The tablet compression test was conducted using a TYPE-M static compressor manufactured by Maekawa Testing Machinery Co., Ltd., equipped with a 10mm diameter round, flat punch and a corresponding die. 300mg of the tablet was filled into each die cavity and compressed. The compression pressures were set to 5, 10, and 15kN, and each test was repeated three times.
[0147] [Table 2]
[0148] Tablets were manufactured to evaluate the compressibility of magnesium glycinate with different degrees of crystallinity, and their strength was evaluated as tensile strength. The results are shown in Table 3.
[0149] In all test examples, tensile strength improved with increasing tablet compression pressure, but decreased with increasing crystallinity. Generally, tensile strength is 100 N / cm². 2It is believed that a certain degree of hardness is sufficient for distribution, and tablets made with magnesium glycinate with a crystallinity of 0-0.81 exhibited sufficient hardness despite a high content of 66.7%. On the other hand, the commercially available comparative example was a dihydrate crystal that did not contain amorphous material, and the tablets produced using it had low strength and were not practically suitable for tablet production.
[0150] [Table 3] [Industrial applicability]
[0151] The magnesium glycinate disclosed herein exhibits good compressive deformability. Furthermore, tablets obtained from the magnesium glycinate disclosed herein have good tensile strength. Therefore, it is expected that it will be possible to obtain tablets by compressing magnesium glycinate and maintain the stability of said tablets. For this reason, the magnesium glycinate disclosed herein is preferably used in foods and beverages and pharmaceuticals. Furthermore, the magnesium glycinate disclosed herein is preferably used in the manufacturing methods of foods and beverages and pharmaceuticals.
Claims
1. In X-ray powder diffraction spectra, Let S1 be the area of an amorphous peak where a local maximum exists in the range 20° ≤ 2θ ≤ 30° and the full width at half maximum is 2° or more. When S2 is the area obtained by subtracting the sum of the areas of peaks attributed to magnesium hydroxide in the range 5° ≤ 2θ ≤ 70° from the sum of the areas of crystal peaks whose maximum value exists in the range 5° ≤ 2θ ≤ 70° and whose full width at half maximum is less than 1°, Magnesium glycinate having a crystallinity expressed as S2 / (S1+S2) between 0 and 0.
9.
2. The magnesium glycinate according to claim 1, wherein, in thermogravimetric analysis, the weight loss rate at 400°C is 40% by mass or less, based on the weight at 50°C.
3. Magnesium glycinate according to claim 1, wherein the degree of crystallinity is 0 or more and 0.81 or less.
4. A food or pharmaceutical product comprising magnesium glycinate as described in any one of claims 1 to 3.
5. A method for producing food or pharmaceuticals using magnesium glycinate as described in any one of claims 1 to 3.
6. A magnesium glycinate tablet comprising magnesium glycinate according to any one of claims 1 to 3.
7. The tensile strength when compressed with a tableting pressure of 5 kN per tablet is 100 N / cm². 2 More than 500N / cm 2 The following are magnesium glycinate tablets.
8. The process includes a step of reacting glycine with a magnesium raw material to obtain magnesium glycinate. A method for producing magnesium glycinate, wherein the magnesium raw material includes one or more selected from magnesium hydroxide and magnesium oxide.
9. The process includes a step of spray-drying a slurry containing glycine and magnesium raw materials to obtain magnesium glycinate. The aforementioned magnesium raw material includes one or more selected from magnesium hydroxide and magnesium oxide. The solid content concentration of the slurry is 9.1% by mass or more and 41.7% by mass or less. A method for producing magnesium glycinate, wherein the slurry temperature immediately before spraying is between 20°C and 90°C.
10. The method for producing magnesium glycinate according to claim 8 or 9, wherein the magnesium raw material includes magnesium hydroxide.
11. The method for producing magnesium glycinate according to claim 8 or 9, wherein the total content of iron and manganese in the magnesium raw material is 0 ppm by mass or more and 270 ppm by mass or less, relative to the total amount of the magnesium raw material.
12. The method for producing magnesium glycinate according to claim 8 or 9, wherein the magnesium raw material comprises magnesium hydroxide and magnesium oxide, and the magnesium hydroxide content is 20% by mass or more in the magnesium raw material.
Citation Information
Patent Citations
Method for preparing metal organic acid chelate
JP2005145822A
Energy-efficient, solvent-free method for the production of metal chelates
JP2020517602A
Crystal polymorph of magnesium glycinate dihydrate and process for its preparation
US20140186408A1